Characteristics Of Briquettes From Tamarind Branch (Tamarindus indica) And Coconut Shell (Cocos nucifera) With Starch Adhesive - Muklis Mulyadin; Devi Tanggasari (Protech Biosystems Journal, 2024)
Natural resources in Indonesia are very abundant, but there are still some that are not utilised properly so that they only become waste polluting the environment, one of which is acid wood. This waste can be innovated into briquettes. This study aims to identify the characteristics of briquettes from tamarind wood and coconut shells with starch adhesive, including moisture content, ash, volatile substances, bound carbon, and calorific value. This study uses a complete randomised design (CRD) as a tool to analyse significant data at the 0.05% level. Each concentration involves a variation of composition between tamarind wood charcoal and coconut shell charcoal, with additional starch adhesive in the ratio of 90%:10%, 45%:45%:10%, and 50%:40%:10%. Each sample will then be analysed for moisture content, ash content, volatile matter content, bound carbon content, and calorific value.  The results showed that the composition of the material mixture greatly affected the characteristics of the briquettes. The lowest average value of moisture content is at concentration P1 with a value of 1.69%, the lowest value in ash content is at concentration P1 with a value of 5.06%, the lowest volatile substance content is at concentration P1 with a value of 13.34%, the highest bound carbon is at concentration P3 with a value of 29.21% and the highest calorific value is at concentration P3 with a value of 6690 cal/gram. The characteristics that meet the SNI NO. 01/6235/2000 standards are only moisture content and calorific value, with the specified standards for moisture content <8% and calorific value >5,000. So from all five testing parameters of moisture content, ash content, volatile substance content, bound carbon content and calorific value, the best treatment was treatment P1 with 90% KA concentration: 10% adhesive.